THC (Δ9‐Tetrahydrocannabinol) Exerts Neuroprotective Effect in Glutamate‐affected Murine Primary Mesencephalic Cultures Through Restoring Mitochondrial Membrane Potential and Anti‐apoptosis Involving CB1 Receptor‐dependent Mechanism. (22nd September 2016) - Nguyen, Chi Huu; Krewenka, Christopher; Radad, Khaled; Kranner, Barbara; Huber, Alexandra; Duvigneau, Johanna Catharina; Miller, Ingrid; Moldzio, Rudolf
Abstract : Aging‐related neurodegenerative diseases, such as Parkinson's disease (PD) or related disorders, are an increasing societal and economic burden worldwide. Δ9‐Tetrahydrocannabinol (THC) is discussed as a neuroprotective agent in several in vitro and in vivo models of brain injury. However, the mechanisms by which THC exhibits neuroprotective properties are not completely understood. In the present study, we investigated neuroprotective mechanisms of THC in glutamate‐induced neurotoxicity in primary murine mesencephalic cultures, as a culture model for PD. Glutamate was administered for 48 h with or without concomitant THC treatment. Immunocytochemistry staining and resazurin assay were used to evaluate cell viability. Furthermore, superoxide levels, caspase‐3 activity, and mitochondrial membrane potential were determined to explore the mode of action of this compound. THC protected dopaminergic neurons and other cell types of primary dissociated cultures from glutamate‐induced neurotoxicity. Moreover, THC significantly counteracted the glutamate‐induced mitochondrial membrane depolarization and apoptosis. SR141716A, a CB1 receptor antagonist, concentration‐dependently blocked the protective effect of THC in primary mesencephalic cultures. In conclusion, THC exerts anti‐apoptotic and restores mitochondrial membrane potential via a mechanism dependent on CB1 receptor. It strengthens the fact that THC has a benefit on degenerative cellular processes occurring, among others, in PD and other neurodegenerative diseases by slowing down the progression of neuronal cell death. Copyright © 2016 John Wiley & Sons, Ltd.